Estudo de impacto de vizinhança: avaliação de impactos gerados por supermercados em cidades de portes diferentes - Molina Junior, Vitor Eduardo (Universidade Federal de São Carlos, 2011)
The Law #10.257/2001 creates some instruments for urban management, among which the Study of Neighborhood Impact (EIV), which despite being required by this law, still hasn t been convincingly regulated by the municipal governments. The present thesis deals with the Study of Neighborhood Impact applied to supermarkets in cities of different sizes (Ribeirao Preto, Sao Carlos and Ilha Solteira) considering their local and regional impacts. The objectives of this research were to identify, present and evaluate the post-building impact related to this kind of enterprise, its valuation, the identification of its influence areas and the related policy acts. In order to reach these objectives, a combination of System of Geographic Information, cross-impact matrix, application of questionnaire and in loco data collection has been used. As a result, it has been verified that the impacts occur independently on the size of the enterprise and of the city. However, they do occur in different magnitudes, and the location of the enterprise in the urban environment is a relevant factor for minimizing them. Still, the verification of attributions to the physical environment in the analysis of the impacts has been considered important in measuring them, so as to include the environmental aspects together with the urban and socio-economic ones in the characterization and analysis of the impacts. Therefore, the EIV sets itself up as an instrument of urban management, allowing more efficient management to urban conflicts and contributing with sustainable development of urban environment.
Keywords: Planejamento urbano; Estudo de impacto de vizinhança; Supermercados; Geoprocessamento; Study of neighborhood impact; Supermarkets; Geoprocessing; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL